Ultimate strength prediction of steel–concrete composite cellular beams with PCHCS. (1st June 2021) - Ferreira, Felipe Piana Vendramell; Tsavdaridis, Konstantinos Daniel; Martins, Carlos Humberto; De Nardin, Silvana
Highlights: A finite element model of composite cellular beams with PCHCS was developed. A parametric study was carried out by geometrical non-linear analyses. Symmetric and asymmetric section were considered. The predominant failure mode was the web post buckling. The strength of the composite cellular beams was not limited only by cellular beam. Abstract: This paper aims to predict the ultimate behavior of steel–concrete composite cellular beams using precast hollow core slabs. A finite element model is developed by geometrical non-linear analysis. A parametric study is carried out, considering symmetric and asymmetric sections with precast hollow core slabs. The key parameters such as the web-post width and the opening diameter are varied, as well as the presence of the concrete topping. A total of 120 analyses were performed. The results are compared with typical composite slab models using cast in-situ concrete. For symmetrical sections, considering the hollow core slabs, although some observations occurred with the formation of the plastic mechanism, the predominant failure mode was the web-post buckling. For asymmetric sections, the predominant failure mode was the combination of the plastic mechanism with the web-post buckling accompanied by the shear connector rupture. In both cases, considering symmetrical and asymmetrical sections, excessive cracking was observed in the upper part of the hollow core slab. In cases where the end-post was greater than the web-post, there was damage at the upper region of the hollow core slab/concrete topping, close to the support. The numerical models of composite cellular beams with hollow core slabs, when compared with the models of composite cellular beams with composite slabs, showed greater efficiency in structural behavior. The results imply that the strength of the composite cellular beams was not limited only by the strength of the steel cellular beam, but also, of the slab, due to the resistance to shear stress.